One Direction [videorecording (DVD)] : this is us (Columbia Pictures Industries, Inc., 2013)
An intimate all-access look at life on the road for the global music phenomenon. Weaved with stunning live concert footage, this inspiring feature film tells the remarkable story of Niall, Zayn, Liam, Harry, and Louis's meteoric rise to fame, from their humble hometown beginnings and competing on the X-Factor to conquering the world and performing at London's famed O2 Arena. Hear it from the boys themselves and see through their own eyes what it's really like to be One Direction.